Analysis and suppression of high-frequency oscillation between converter-based source and loads in an island power system. (May 2020) - Wu, Wenhua; Xie, Zhiwei; Chen, Yandong; Liu, Jinming; Guo, Jian; Xu, Yuancan; Wang, Haining; Luo, An
Highlights: A small-signal sequence impedance model of the island power system is built by harmonic linearization method. It is found that the output sequence impedance of the source PWM inverter in the system is not affected by the stable operating point. Based on the impedance model, the influence of load type and load power on the stability of the island power system is analyzed. The essential reason of the high-frequency oscillation is that the capacitive output impedance of the source PWM inverter does not match the inductive output impedance of the load PWM rectifier at high-frequency areas. An impedance reconstruction control for the source PWM inverter is proposed, which improves the phase of the output sequence impedance of the source PWM inverter at high-frequency areas to effectively suppress the high-frequency oscillation of the island power system. Abstract: In island power system with strong mutual interaction of power electronic devices, stability problems such as high-frequency oscillation are prone to occur. Firstly, a small-signal sequence impedance model of an island power system is built by harmonic linearization method. It is found that the output sequence impedance of the source PWM inverter in the system is not affected by the stable operating point, but the input sequence impedance of the load PWM rectifier will decrease with the increase of power. Then, based on the sequence impedance model and Nyquist stability criterion, the influence of load type and load power on stability of the island power system is analyzed, which can reveal that high-frequency oscillation occurs when the source PWM inverter interacts with the load PWM rectifier. The essential reason of the high-frequency oscillation is that the capacitive output impedance of the source PWM inverter does not match the inductive output impedance of the load PWM rectifier at high-frequency areas. Aiming at this issue, an impedance reconstruction control for the source PWM inverter is proposed, which improves the phase of the output sequence impedance of the source PWM inverter at high-frequency areas to effectively suppress the high-frequency oscillation of the system. Finally, experiment results verify the correctness of analysis and effectiveness of the proposed control strategy.